The practice of catheter cryoablation for cardiac arrhythmias - Chan, Ngai-Yin (John Wiley & Sons, 2014)
"A comprehensive guide, with self-assessment to the clinical application of this exciting alternative treatment for atrial fibrialtion and other cardiac arrhythmias"--Provided by publisher.